Plan de turismo comunitario de la Casa de Hospedaje Mushuk Kawsay parroquia Angochagua-cantón Ibarra, provincia de Imbabura - Benavides Limaico, Mireya Fernanda (2015)
This project is focused on the elaboration of a Community Plan of Tourism, located in the Parish of Angochagua - Canton Ibarra - Province of Imbabura, it will serve to promote tourism in the community of Zuleta, this will be teaming with "Casa de Hospedaje MUSHUK KAWSAY", in order to achieve new goals and also improving the lifestyle of the community. The research was based on the problem tree, where they were exposed, the causes and effects that exist both in the community and in the Lodging, resulting in a lack of knowledge about community tourism was observed by local community members Zuleta However, by the lack of organization and communication, either by the president of the community and its residents has not been able to exploit its tourist attractions as they should, even in the parish of Angochagua, there are a wide variety of tourist attractions as manifestations cultural. For the project, it is proposed to make some changes in the hosting mainly be the implementation of tourism packages for its customers, in order to retain and attract more tourists to Zuleta, and essentially to the "Casa de Hospedaje MUSHUK KAWSAY" creating jobs for the community members themselves.